A Single Blind In vitro UV Spectrophotometry Quantitative Assay of Different Pharmaceutical Oral Preparartion of 500mg Metformin - Sheela D2, Tharini C B3, K.Latha1* (Recent Research in Science and Technology, 2010)
Aim: To find out the chemical equivalence of metformin 500mg of five different manufacturers. Materials and methods: Quantitative analysis of five different brand of metformin 500mg was done by spectrophotometry. The reproducibility was tested. Throughout the study quantitative analyst was kept blind of the product. Results: The results were analysed to find out the chemical equivalence of metformin 500mg. It was found to be chemically equivalent. Conclusion: The above study revealed the assay purity of metformin 500mg of five different brands, to that of Indian pharmacopoeia prescribed standards.